Research of distribution pattern of allelic genes and genotypes of C/A polymorphism of COL1A1_1 collagen gene (RS1107946) in children with nasal obstruction of allergic genesis and orthodontic pathology - Т. Ye. Shumna; O. M. Kamyshnyi; Т. P. Zinchenko (Zaporozhye State Medical University, 2018)
Purpose. Determination of the genotypes of C/A polymorphism of COL1A1_1 collagen gene (rs1107946) and patterns of distribution of allelic genes in children with nasal obstruction and orthodontic pathology. Materials and methods. A molecular-genetic study for determination of C/A polymorphism of COL1A1_1 collagen gene (rs1107946) was performed in 99 children at the age of 6 to 17 years, for 11 months and 30 days inclusive; 30 children of which had nasal obstruction due to allergic rhinitis without abnormal distal occlusion (the first group); 23 children had just the distal occlusion (the second group); 26 children had allergic rhinitis and distal occlusion (the third group); 20 almost healthy children (the fourth group). Genotyping was performed by the polymerase chain reaction method (Applied Biosystems, USA) using the total DNA samples isolated from whole venous blood using a set of reagents SNP-Screen (Syntol manufacturer) on the CFX96TM Real-Time PCR Detection Systems amplifier (Bio-Rad Laboratories, Inc., USA). Non-parametric statistic methods of the licensed software package Statistica for Windows 6.1.RU, serial number AXXR712D833214SAN5 was used for processing the research results. Results. Molecular-genetic study of the distribution patterns of allelic genes and genotypes of the C/A polymorphism of the COL1A1_1 (rs1107946) collagen gene in the examined children showed that the frequency of occurrence of the C allele was significantly higher than the A allele (71.72 % and 28.28 %, respectively). In this case, the homozygous C/C genotype was registered most often (68.69 %), homozygous genotype A/A (25.25 %) was rarely registered and heterozygous C/A (6.06 %) was very rarely registered. In the observation groups, in children with allergic rhinitis, distal occlusion and a combination of allergic and orthodontic pathology, the genotypes had the following distribution: the C/C genotype - 76.67 %; 34.78 %; 73.00 %; A/A genotype - 20.00 %; 56.52 %; 17.39 %; A/C genotype - 3.33 %; 8.70 %; 11.54 %. The occurrence frequency of alleles of the C/A polymorphism of the COL1A1_1 collagen gene (rs1107946) in the examined children showed that the children with distal occlusion were significantly frequent carriers of A allele (60.87 %), whereas the carriers of C allele were predominantly children with allergic rhinitis (78.33 %), with combined allergic and orthodontic pathology (78.85 %) and healthy (90.00 %), P < 0.05. The correlation between the results of the study conducted in groups of children with the distal occlusion and practically healthy showed that the sensitivity of the presence of A allelic gene was equal to 60.87 %, specificity - 90.00 %, accuracy - 61.54 %. Since the sensitivity and specificity of the diagnostic test exceeded 50.00 %, the prognostic value for the positive result was equal to 87.50 % and for the negative result - 66.67 % and confirm this prognostic significance for the development of the orthodontic pathology in children. This will allow improving the preventive measures in children with orthodontic pathology. Conclusions. The molecular-genetic studies for determining the A allele (rs1107946) of the COL1A1_1 collagen gene in children could be recommended to determine the risk of development and the need for early prevention of the distal occlusion in children.